Social networks near and far: The role of bonding and bridging social capital for assets of the rural poor - Mogues, Tewodaj (John Wiley & Sons, 2019)
With formal insurance and credit markets either absent or inaccessible to rural agents in most poor rural economies, social networks play a highly important role in mitigating the risks that agricultural households face. These kinds of informal insurance schemes are presumed to be most effective in the face of idiosyncratic risk. However, social mechanisms also exist in developing countries that may reduce locally correlated risk such as the adverse economic effects of climatic conditions that affect multiple residents in a village. This paper analyzes the role of localized (bonding) and of spatially dispersed (bridging) social capital in mitigating the impact of idiosyncratic and of locally correlated shocks on farm households’ livestock endowments. Using dynamic panel generalized method of moments (GMM) system estimation with seven‐period panel dataset of over 400 households, we find that bonding social capital is able to protect households’ livestock assets against idiosyncratic shocks, but bridging social capital does not play a role in mitigating the impact of correlated shocks. The results hold up to multiple robustness checks. A test of different hypotheses about the nature of these assets’ trajectories rejects the asset poverty trap hypothesis, and instead finds that livestock asset dynamics are characterized by a single stable equilibrium.